Application and modelling of ultrasonic transducers using 1-3 piezoelectric composites with structured electrodes - Dreiling, Dmitrij; Itner, Dominik; Feldmann, Nadine; Scheidemann, Claus; Gravenkamp, Hauke; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)
Waveguide-based methods can be used for the non-destructive determination of acoustic material parameters. One of these methods is based on transmission measurements of cylindrical polymeric specimens. Here, the experimental setup consists of two transducers, which excite and receive the waveguide modes at the faces of the cylinder. The measurement, as well as a forward model, are used to determine material parameters of the polymeric specimen in an inverse approach. 1-3 piezoelectric composites are used as an active element because they can be approximated by a thickness vibration only. This allows an easy identification of Mason model parameters to characterise the transducers’ vibration behaviour. However, sensitivity analysis shows a high uncertainty in the determination of the mechanical shear parameters due to the uniform excitation. To increase the sensitivity to these shear motions, arbitrary excitations were investigated by means of numerical simulation. In order to be able to realise the determined optimal excitation, new transducer prototypes were designed. By subdividing the electrodes of the active element, for example, ring-shaped excitation is feasible. Furthermore, it can be shown that modelling these transducers with a one-dimensional Mason model is sufficient.